A visual language for temporal specifications based on Spider diagrams - Bottoni, Paolo; Fish, Andrew (Electronic Communications of the EASST, 2011)
Spider Diagrams are a well-established visual language to specify sets, their relationships, and constraints on their cardinalities. However, they do not support evolution of specifications, where one wants to state that under certain circumstances a specification becomes invalid and a new one must be used, nor transformation of specifications, where one needs operators to manipulate specifications. In this paper, we attack the first problem by developing a new system of timed Spider Diagrams which allow modellers to indicate the temporal range of validity of a specification. The approach is illustrated with examples of policies for library management.